Faktor Penting dalam Meningkatkan Loyalitas Pelanggan Jepunayu Salon - I.A. Oka Martini; Ni Kadek Dwi Anatasya (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
The phenomenon of negative reviews found at JEPUNAYU Salon reflects customer dissatisfaction that not only damages the salon’s reputation but also potentially erodes satisfaction levels and, ultimately, affects customer loyalty. This study aims to identify the influence of several variables, including service quality, store atmosphere, customer satisfaction, and customer loyalty at JEPUNAYU Salon. The research involved 108 respondents, and the data were processed using SmartPLS 4 software. This research employed quantitative data obtained from both primary and secondary sources. Data collection was conducted through questionnaires, and data analysis techniques included validity testing, reliability testing, measurement model (outer model), structural model (inner model), and hypothesis testing. The results show that service quality has a positive and significant effect on customer loyalty at JEPUNAYU Salon. Service quality also has a positive and significant effect on customer satisfaction. Store atmosphere positively and significantly affects customer satisfaction and customer loyalty. Furthermore, customer satisfaction positively and significantly affects customer loyalty. Customer satisfaction serves as a mediating variable that strengthens the influence of service quality on customer loyalty, as well as mediating the relationship between store atmosphere and customer loyalty at JEPUNAYU Salon. Future research is suggested to include additional variables to obtain more comprehensive results. Moreover, subsequent studies can be conducted in other service sectors to examine the consistency of the effects of service quality and store atmosphere on customer loyalty.